Comparison of Endovascular Therapy for Ruptured Cerebral Aneurysm during Spasm and Nonspasm Period - Kamide, Tomoya; Misaki, Kouichi; Tsutsui, Taishi; Nambu, Iku; Yoshikawa, Akifumi; Nakada, Mitsutoshi (Asian Journal of Neurosurgery, 2022)
Objective Cerebral vasospasm complicates the treatment of aneurysmal subarachnoid hemorrhage, and the optimal timing of surgery for ruptured intracranial aneurysm diagnosed during the cerebral vasospasm period has been a matter of debate. This study aimed to clarify the differences in endovascular treatment outcomes between the timing of intervention during spasm and nonspasm.Methods and Materials We retrospectively reviewed 68 consecutive patients with ruptured cerebral aneurysms who underwent coil embolization between January 2016 and March 2021. Clinical presentations, radiographic findings, and outcomes were retrospectively reviewed and compared between patients who were treated at the time of spasm and nonspasm. Information regarding the following clinical characteristics was collected: age, sex, World Federation of Neurosurgical Societies (WFNS) grade on admission, aneurysm morphology, treatment result, and outcome. We defined from day 4 to day 14 as the timing of spasm, and vasospasm as more than 30% narrowing of the proximal anterior cerebral artery, middle cerebral artery, and internal carotid artery segment during the second examination compared with the first. The chi-squared test or Fisher's exact test were performed to evaluate the covariates for binary categorical dependent variables as appropriate, and nonnormal variables were compared using the Mann–Whitney U test.Results Ten patients (14.7%) underwent coil embolization at the time of vasospasm. Age, sex, WFNS grade, and aneurysm morphology were not different between the spasm and nonspasm groups. Additionally, there were no significant between-group differences in volume embolization ratio, procedure-related complications, occurrence of delayed cerebral ischemia, and outcome at discharge.Conclusion There were no significant between-group differences in treatment results and outcomes between the spasm and nonspasm groups. Endovascular treatment at the time of vasospasm could be the optimal treatment method for ruptured cerebral aneurysms.
Keywords: endovascular treatment; cerebral aneurysm; vasospasm; treatment outcome